The bleeding and clotting time analysis of the stem extract of Musa paradisiaca var. sapientum (L.) Kunze on hemostatic response - Setia Budi, Hendrik; Setyari Juliastuti, Wisnu; Putri Sulistyowati, Yuniar (Jordan Journal of Pharmaceutical Sciences, 2021)
A herbal medicine that can be used to accelerate bleeding is the Ambonese banana stem sap (Musa paradisiaca var. Sapientum) through secretion of Adenosin Diphosphate (ADP) and von Willebrand Factor (vWF) in the process of platelet adhesion on the injury vessels. The aim of this study to test the influence of Ambonese banana stem extract in a concentration of 25%, 50% and 100% against hemostatic response on mice. 24 animal study were randomly assigned into four groups. Group 1 was the control, group of 2 was given 25% extract concentration, group of 3 was given 50% extract concentration and group of 4 was given 100% extract concentration of Ambonese banana stem per-oral. Then all the groups were examined their bleeding and clotting time. The administration of Ambonese banana stem extract at the concentrations of 25%, 50 %, and 100% significantly shortened both bleeding time and clotting time compared to control group (p = 0.00). The group with 100% extract of the Ambonese banana stem having the shortest bleeding time and clotting time. The conclusions of this study showed Ambonese banana stem extract has potential as the hemostatic agent by shortening bleeding and clotting time on mice.